Persian historic urban landscapes : interpreting and managing Maibud over 6000 years - Esfanjary, Eisa (Edinburgh University Press, 2017)
"Persian cities are part of a corridor of civilisation with settlements straddling thousands of years. Taking Maibud as a case study, Eisa Esfanjary traces the evolution of ancient settlements chronologically, thematically and methodologically. Maibud provides the basis from which a new interpretive approach is developed, being a city that has a history of several millennia yet has a scale that renders it manageable with archaeological remains that range across several phases of building development. An archetypal example of middle-sized Persian cities, it affords insights into the entire urban landscape and its spatial, functional and morphological iterations. Within this overall picture, a methodology is developed to explore various morphological elements of the city, the three key components of which are the town plan, the building type, and construction materials. The inter-relationships between these three components are explained in order to formulate an approach to support the management and conservation of the historic urban landscape. Combining a rigorous survey and observation of the standing structures with scarce archaeological and written sources, this book sheds light on Islamic urbanism in general and Islamic urbanism in Iran particularly."--Publisher website